Feeling good mother/father and other regimes. LGBT people’s emotions and parenthoods: - Alday-Mondaca, Carolina; Castañeda-Rentería, Liliana; Lay-Lisboa, Siu (Anales de Psicología / Annals of Psychology, 2024)
In this article, we analyze and discuss the emotional dimension that LGBT people associate with the exercise of motherhood/fatherhood. Based on feminist theory and subalternity and intersectionality theory contributions, we applied the biographical method to a dialogical-recursive investigative process. Participants were 21 LGBT people and key informants, belonging to academia, psychotherapy, politics, and diversity activism, over 18 years old, from Chile (16), Mexico (4), and Colombia (1); the participants were people between 21 and 57 years of age, with a mean age of 37.19 and a standard deviation of 10.03. We found emotions related to the social mandate to "be a good mother/father"; emotions resulting from social situations such as discrimination and legal lack of protection, and emotions derived from the parenting experience. We conclude that repression/resistance dynamics go through the bodies, and emotions are fundamental to this incarnation. Given this, the development of research focused on emotion can open ways to achieve more just societies through cultivated sentimentality, societies aware of the type of bonds that keep us as worthy members of a society and the performative effect of our emotional demands.